SKUTKI OPRÓŻNIENIA URZĘDU PREZYDENTA W POLSKICH KONSTYTUCJACH XX WIEKU - Bielarczyk, Piotr (Zeszyty Prawnicze, 2016)
THE CONSEQUENCES OF A VACANCY IN THE OFFICE OF THE PRESIDENT UNDER 20TH CENTURY POLISH CONSTITUTIONS Summary The article discusses the consequences of a vacancy in the office of the President of the Republic in 20th-century Polish constitutions. A vacancy in the office of the President takes place in the event of death, resignation, the election of a President being found invalid, among other possibilities. The problem of succession to the office of President became particularly significant in connection with the Smolensk air disaster of 10 April 2010, which took the life of President Lech Kaczyński. This is why particular attention was paid to the provisions of the current Constitution adopted in 1997, pursuant to which the Speaker of the Sejm (lower house of Parliament) served as interim President. The article evaluates these provisions and their application from April to August 2010, i.e. until the swearing-in of the newly-elected President.